2011
DOI: 10.1038/onc.2011.106
|View full text |Cite
|
Sign up to set email alerts
|

Loss of AF6/afadin, a marker of poor outcome in breast cancer, induces cell migration, invasiveness and tumor growth

Abstract: Afadin/AF6, an F-actin-binding protein, is ubiquitously expressed in epithelia and has a key role during development, through its regulatory role in cell-cell junction organization. Afadin loss of expression in 15% of breast carcinoma is associated with adverse prognosis and increased risk of metastatic relapse. To determine the role of afadin in breast cancer, we studied the functional consequences of afadin protein extinction using in vitro and in vivo models. Three different breast cancer cell lines represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
53
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 43 publications
2
53
0
Order By: Relevance
“…Stable AF6-overexpressing Capan-1 and Capan-2 cell lines were generated using lentiviral vector pRRL-AF6FL; this vector, which encodes full-length AF6, was generously provided by Dr M Lopez (University of the Mediterranee, Marseille, France). Lentivirus production and cell-line constructions were performed as described previously 45 ; in brief, the virus particles were produced by transient transfection into 293T cells seeded in 6-cm dishes with 2.7 mg of the packaging construct, 0.9 mg of the construct that express the vesicular stomatitis virus glycoprotein and 2.7 mg of the pRRL-AF6FL vector, and the media from the transfected cells was collected as the cells were re-fed each day for 3-4 days. The virus-containing media was pooled, filtered and used to generate AF6-overexpressing stable cell lines.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stable AF6-overexpressing Capan-1 and Capan-2 cell lines were generated using lentiviral vector pRRL-AF6FL; this vector, which encodes full-length AF6, was generously provided by Dr M Lopez (University of the Mediterranee, Marseille, France). Lentivirus production and cell-line constructions were performed as described previously 45 ; in brief, the virus particles were produced by transient transfection into 293T cells seeded in 6-cm dishes with 2.7 mg of the packaging construct, 0.9 mg of the construct that express the vesicular stomatitis virus glycoprotein and 2.7 mg of the pRRL-AF6FL vector, and the media from the transfected cells was collected as the cells were re-fed each day for 3-4 days. The virus-containing media was pooled, filtered and used to generate AF6-overexpressing stable cell lines.…”
Section: Methodsmentioning
confidence: 99%
“…The phenotypic changes observed with these mice include disorganization of the ectoderm, impaired migration of the mesoderm and loss of somites or other structures derived from both the ectoderm and the mesoderm 10,11 . Recently, expression of the AF6 gene was found to be aberrant in multiple cancer types, including leukaemia, ovarian and breast cancers 3,4,[12][13][14][15][16] , but the specific roles that AF6 might play in tumorigenesis remain unclear.…”
mentioning
confidence: 99%
“…Previous studies have indicated that Afadin regulates migration and cell-cell adhesion in other cell types, including fibroblasts and epithelial cells (28,29). A previous study indicated that Afadin is associated with angiogenesis through Rap1 signaling (30).…”
Section: Discussionmentioning
confidence: 99%
“…Occludin has four known splice variants (52), and knockout studies of the parent molecule have indicated its importance in tight junction stability and maintenance in epithelial cells (53). Additionally, occludin has been established as a regulator of epithelial cell migration, with phosphorylation at the Y473 residue resulting in PI3K activation at the leading edge of migratory cells (54).…”
Section: Occludinmentioning
confidence: 99%